Evaluation Of Dry Eye Disease Using Clinical Tests In Routine Opd Patients Schirmer Test, Tbut, Symptom Scoring. - Zeeshan Tahir, Muhammad; Waseem, Muhammad; Rafiq, Muhammad; Khan, Jehanzeb; Hamza, Syed Amir; Sultan, Maria (Journal of Neonatal Surgery, 2025)
Background: Dry eye disease is typically referred to as a multifactorial disease because there are multiple causes for this disease. This is especially true when dry eye affects quality of life. With the Schemer test and TBUT, which are simple, readily available tests to evaluate dry eye, this disease is still, for the most part, left unappreciated. Objectives: To assess dry eye disease among routine outpatient department (OPD) attendees by performing Schemer testing, tear break-up time (TBUT) assessment, and symptom scoring, and to determine the relationship between subjective symptoms and objective clinical findings to support timely and accurate diagnosis. Methodology: this study conducted in Gajju Khan Medical College Swabi from jan 2023 to jan 2024. 100 patients aged 18 years or older who were visiting the outpatient department surveys were conducted during a typical workday. Participants were asked to provide informed consent, after which demographic information was collected. Patients were asked to complete a standardized symptom questionnaire, followed by the determination of TBUT (tear break-up time) and a Shimmer test. Dry eye levels were determined using symptom and test scores. The information was analyzed using SPSS software and the t-test or chi-squared test, where applicable; p < 0.05 was the level of statistical significance. Results: A total of 100 patients were evaluated, with a mean age of 43.1 ± 13.4 years. Dry eye disease was identified in 72 patients (60%) based on combined diagnostic criteria. Abnormal TBUT was present in 67 patients (55.8%), while 48 patients (40%) showed reduced Schemer values. Symptom scoring categorized 26% as mild, 24% as moderate, and 10% as severe dry eye. Females demonstrated a significantly higher frequency of abnormal TBUT compared to males (p = 0.02). Symptom severity showed a strong positive correlation with reduced TBUT (p = 0.01) and a moderate correlation with low Schemer values (p = 0.03). Conclusion: Dry eye disease was prevalent amongst attendees of OPD. There was significance in symptom scoring, TBUT, and Schmerz values; therefore, both subjective and objective measures are critical to enhance detection and management.